A contribution to the oceanology of the Prince Edward Islands - Parker, Llewellyn Derek (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1985)
While the terrestrial ecosystem of the Prince Edward Island Group has been subject to intensive research, the marine ecosystem has to a large extent been neglected. This together with the possible existence of an "island effect" at these islands, as was first proposed after the visit to these islands of the French vessel Marion Dufresne, led to the initiation of a programme to determine the distribution of standing stocks and the productivity of phytoplankton and zooplankton in the neritic seas of these islands. To do this and before a detailed biological survey could be attempted, it was first necessary to define the physical and chemical properties of the circuminsular waters. This dissertation discusses the results of several surveys to these islands in the light of a possible "island effect" and comments upon processes likely to influence such an effect
Keywords: Oceanography -- Prince Edward Islands